CGIAR Research Program on Policies, Institutions, and Markets - Plan of Work and Budget 2020 - CGIAR Research Program on Policies, Institutions, and Markets (CGIAR Research Program on Policies, Institutions, and Markets, 2020)
In 2019 PIM completed the participatory priority-setting exercise started in 2018 to update the priorities for the program’s final 2019-2021 period. As a conclusion of this exercise, the framework of the Phase 2 proposal as well as the flagships’ impact pathways were reaffirmed as highly relevant. At program level, five cross-cutting thematic areas were flagged as deserving more emphasis, mostly because (i) they are of key interest to policy makers, funding agencies, and CGIAR and/or (ii) they are addressed in multiple flagships of PIM and will benefit from more coordinated investments. These high-impact areas are: improved nutrition; effects of and responses to climate change; gender equality and women’s empowerment; employment opportunities for rural people, especially for the youth; and transformation of agrifood systems. In 2020 several new activities are developed in alignment with one or more of these areas. PIM’s targeted contribution to SLO2 on improved nutrition is becoming more significant, and work in this area – previously limited to Flagship 4 (social protection) – is expanding to almost all other flagships.